Western Australian children with acute lymphoblastic leukemia are taller at diagnosis than unaffected children of the same age and sex - Davis, E; Cole, C; de Klerk, N; Milne, E; Jacoby, P (My University, 2011)
Background Acute lymphoblastic leukemia (ALL) is the commonest childhood malignancy in Australian children. Recently published data from Western Australia suggest a link between proportion of optimal birth weight and the risk of ALL, but few studies have investigated the relationship between growth during infancy and early childhood and risk of leukemia. The aim of this study was to determine whether children diagnosed with ALL in Western Australia were taller at the time of diagnosis than children of the same age and sex in the general population. Methods Records of children diagnosed with ALL between January 1984 and June 2008 were accessed. Height before the commencement of chemotherapy was recorded and compared to the height of population norms derived from the Longitudinal Study of Australian Children. Results On average, male cases were 0.67 cm (95% CI −0.21, 1.54 cm) taller and female cases were 0.30 cm (95% CI −0.68, 1.28 cm) taller than population controls. Conclusions Conclusions Our results suggest that children diagnosed with ALL in Western Australia are slightly taller than their counterparts in the general population. These findings are consistent with at least one previous study. While this increase in height may be too small to be recognizable clinically, it is consistent with the notion that growth factors play a role in the pathogenesis of ALL beyond infancy.
Keywords: Child Development -- Physical; Childhood and child development; Child Development; Physical; Childhood and child development